A road map for Shymkent Tashkent Khujand economic corridor development. (Metro Manila, Philippines Asian Development Bank, 2020)
The assessment explores the transit of international goods in cities and oblasts administrative divisions or regions in STKEC and and trade regimes in the three countries. The report also identifies and analyzes existing barriers and opportunities for trade expansion. It provides recommendations for various stakeholders on policy measures for improvement under the framework of the STKEC development.
Keywords: Industry and state -- Developing countries; Electronic books